Perbaikan Proses Produksi Pupuk untuk Mengurangi Tingkat Kecacatan - Prasetia, Angga Eka; Wati, Putu Eka Dewi Karunia (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to reduce the defect rate in the production process of granule phosphate and potassium fertilizers at PT X, which includes undersize, oversize, and misshapen product defects. The PDCA method was employed as a quality improvement approach through the stages of Plan, Do, Check, and Action. Pareto Analysis, Histogram, and Fishbone Diagram were used to identify dominant defect types and determine their root causes, while corrective actions were focused on establishing new Standard Operating Procedures (SOP), providing operator training, and adding quality inspection checkpoints at each production stage. The results show a significant reduction in the average phosphate defect from 802 kg to 319 kg, successfully maintaining quality within control limits, and improved consistency in potassium fertilizer quality. This study recommends the implementation of continuous quality monitoring at every process stage to ensure high-quality products.